2012
DOI: 10.1071/an11312
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ruminal microbiota due to rumen content processing and incubation in single-flow continuous-culture fermenters

Abstract: The aim of this study was to investigate the impact of rumen content manipulation and its incubation in an in vitro system on the abundance of some microbial groups and the bacterial diversity of goat rumens. Animals and singleflow continuous-culture fermenters were fed diets differing in forage to concentrate ratio (70 : 30; LC and 30 : 70; HC). Rumen contents were sampled after animals' adaptation to the experimental diets, processed for inoculum preparation and inoculated into fermenters. Fermenter contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In vitro batch incubation is commonly used in short‐term studies, which do not allow the verification of long‐term adaptation of the rumen microbiome to the compounds tested. In addition , in vitro batch cultures do not reflect factors such as continuous absorption of VFAs, neutralization by saliva, and dilution rate of rumen content (Soto, Yáñez‐Ruiz, Cantalapiedra‐Hijar, Vivas, & Molina‐Alcaide, ). For these reasons, further efforts are required to verify safe and effective concentrations of the perspective compounds from this study, which should be able to affect the rumen microbial ecosystem and its fermentation positively in in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro batch incubation is commonly used in short‐term studies, which do not allow the verification of long‐term adaptation of the rumen microbiome to the compounds tested. In addition , in vitro batch cultures do not reflect factors such as continuous absorption of VFAs, neutralization by saliva, and dilution rate of rumen content (Soto, Yáñez‐Ruiz, Cantalapiedra‐Hijar, Vivas, & Molina‐Alcaide, ). For these reasons, further efforts are required to verify safe and effective concentrations of the perspective compounds from this study, which should be able to affect the rumen microbial ecosystem and its fermentation positively in in vivo conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar differences between in vitro and in vivo studies have been observed by Mohammed et al (2004) using Japanese horseradish oil, who reported substantially greater inhibitions of methane production in vitro (89%) than in vivo (18.7%). The disagreement in the effectiveness observed between results obtained in vitro and in vivo with the same doses strongly supports the need for testing in vivo what it is previously observed in vitro and may be explained by a number of factors: (i) the compounds used in this study had very low solubility in water, and therefore the homogenous distribution across the rumen compartments might have not been fully achieved; (ii) the degradation rate of the compounds may differ in vitro and in vivo; and (iii) there is a reported decrease in microbial densities and changes in bacterial community structure when rumen content is processed before inoculation in vitro, which could be attributed to the exposure of microorganisms to oxygen and the discard of the main part of solids during the filtration process (Soto et al, 2012). In addition, the direct extrapolation of concentrations from in vitro to in vivo did not take into account the rumen outflow, which in our conditions, with animals fed restricted intake, was estimated to be around 3%/h (Yáñez-Ruiz et al, 2004).…”
Section: Experiments 3 ( In Vivo)mentioning
confidence: 99%
“…heavily buffered rumen fluid in vitro, different solid and liquid turnover rates, changes induced in the microbial ecosystem when incubated in vitro, such as a decrease in total biomass and community structure, and limited presence of fungi and protozoa; Soto et al, 2012). In addition, in vitro and in vivo studies are normally conducted separately and often no reference compound with a known, consistent effect is included.…”
Section: Introductionmentioning
confidence: 99%
“…Much larger decreases in CH 4 production were observed in vitro (−89%) than in vivo (−18.7%, Table 2), findings that are in agreement a recent meta-analysis (Hristov et al, 2012). Such discrepancies in the effectiveness of test compounds when given in similar doses may be explained by a combination of several factors: (1) test compounds used are typically administered in 1-2 pulses via the ruminal cannula that often coincide with feeding times, and as a consequence might not be rapidly and well mixed with rumen contents; (2) differences in the degradation rate of the active compounds in vitro and in vivo; (3) decrease in microbial density and changes in bacterial community structure of rumen contents during processing as inoculum for in vitro studies associated with the exposure of microorganisms to oxygen and the removal of solids during filtration (Soto et al, 2012); (4) potential washout of these compounds from the rumen or absorption through the rumen wall and (5) adaptation of the rumen microbial ecosystem to the tested compound in vivo that is not emulated by inoculated microbiota in vitro.…”
Section: In Vitro Versus In Vivomentioning
confidence: 99%